Aviation Building, New York World's Fair (Curt Teich & Co.)
The Aviation Building at the New York World's Fair 1939 is designed to give visitors the impression of arriving at a large and busy airport. In the central portion of the structure will be an exhibit of the latest types of planes and of the planes of tomorrow. The dome-like rear portion holds an invisibly suspended transport plane with propellers moving as if in flight. The illusion of motion is to be created by projection of moving clouds and night effects against the curved background, At the floor level will be exhibits of agencies cooperating to increase the safety and speed of air travel. The architect is William Lescaze, with J. Gordon Carr as associate.